2016
DOI: 10.3390/ijerph13111161
|View full text |Cite
|
Sign up to set email alerts
|

Overt Primary Hypothyroidism in an Industrial Area in São Paulo, Brazil: The Impact of Public Disclosure

Abstract: Abstract:Background: Primary hypothyroidism (PH) is the most common thyroid pathology. Purpose: to evaluate the impact of public disclosure of an unexpected number of PH cases on the frequency of patients seeking medical evaluation for endocrinological diseases. Methods: data on 6306 subjects (3356 living in the surroundings of a petrochemical complex and 2950 in a control region) were collected over a 15-year time span. Thyroid function was determined by serum levels of triiodothyronine, thyroxine, free thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…São Paulo State (SP) is the most populous and industrialized state in Brazil with about 45 million inhabitants and 7012 industries [20]. In our previous studies [21,22], which were conducted on a densely populated area of SP, surrounding the Capuava Petrochemical Complex (CPC), we reported overt primary hypothyroidism [22] and the increasing of chronic autoimmune thyroiditis (CAT) incidence over the years [21]. Petroleum processing can emit different organic compounds that can threaten human health [23].…”
Section: Introductionmentioning
confidence: 99%
“…São Paulo State (SP) is the most populous and industrialized state in Brazil with about 45 million inhabitants and 7012 industries [20]. In our previous studies [21,22], which were conducted on a densely populated area of SP, surrounding the Capuava Petrochemical Complex (CPC), we reported overt primary hypothyroidism [22] and the increasing of chronic autoimmune thyroiditis (CAT) incidence over the years [21]. Petroleum processing can emit different organic compounds that can threaten human health [23].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies (Zaccarelli -Marino 2012;Zaccarelli-Marino et al 2016 involved subjects living in a densely populated area of SP surrounding the Capuava Petrochemical Complex (CPC). We reported primary hypothyroidism (PH) (Zaccarelli- Marino et al 2016Marino et al , 2019 and an increase in the incidence of chronic autoimmune thyroiditis (CAT) over the years (Zaccarelli-Marino 2012) and showed evidence that iodine should not be considered the agent responsible for autoimmune thyropathies in Santo André (Marino et al 2009). Some of the results of the current study have been previously reported in the form of an abstract and poster presented at the ABC University Medical Congress (Zacarelli- Marino et al 2016aMarino et al , b, 2017aMarino et al , b, 2018a.…”
Section: Introductionmentioning
confidence: 99%
“…Another study investigated the air pollution relationship with blood pressure alterations and concluded that traffic controllers working outdoor shifts in Santo André presented higher blood pressure during exposure to local pollutants (Chiarelli et al, 2011). In addition, atmospheric pollutants in the CPC area seem to be the highest risk factor for primary hypothyroidism in children and adults, but a considerable increase in the incidence of this disease was observed in residents in the proximity of CPC (Zaccarelli-Marino 2012;Zaccarelli-Marino et al, 2016 and.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies about biomonitoring, population health and VOCs in the atmosphere were carried out in the Great ABC region in the MASP (Saiki et al, 2007;Evo et al, 2011;Pereira et al, 2019;Zaccarelli-Marino, 2012;Zaccarelli-Marino et al, 2016). The biomonitoring of air pollution in the vicinity of the Petrochemical and Industrial Complex (PIC) evidenced the highest concentration of pollutants when compared to the areas of Santo André (part of Great ABC region) that were not under the influence of industries (Saiki et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation